2021
DOI: 10.5664/jcsm.9542
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes of hypoglossal nerve stimulation therapy: current practice, future directions, and research gaps. Proceedings of the 2019 International Sleep Surgery Society Research Forum

Abstract: Hypoglossal nerve stimulation (HGNS) has evolved as a novel and effective therapy for patients with moderate-to-severe obstructive sleep apnea. Despite positive published outcomes of HGNS, there exist uncertainties regarding proper patient selection, surgical technique, and the reporting of outcomes and individual factors that impact therapy effectiveness. According to current guidelines, this therapy is indicated for select patients, and recommendations are based on the Stimulation Therapy for Apnea Reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 100 publications
0
20
0
Order By: Relevance
“…These observations corroborate data from Ng and colleagues which identified decreased expressions of adiponectin and irisin levels in obese OSAS patients in response to CPAP treatment for 3 months [ 36 ]. In our study here, we had a typical BMI distribution in an OSAS cohort treated with HNS [ 37 , 38 ]. Furthermore, about 80% of children with Marfan’s syndrome suffer from OSAS, which is characterized by a present reduction in palatal area and volume and thus underlines the multifactorial etiology of obstructive sleep apnea syndrome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations corroborate data from Ng and colleagues which identified decreased expressions of adiponectin and irisin levels in obese OSAS patients in response to CPAP treatment for 3 months [ 36 ]. In our study here, we had a typical BMI distribution in an OSAS cohort treated with HNS [ 37 , 38 ]. Furthermore, about 80% of children with Marfan’s syndrome suffer from OSAS, which is characterized by a present reduction in palatal area and volume and thus underlines the multifactorial etiology of obstructive sleep apnea syndrome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results have been promising and stable over time, and patients' adherence and satisfaction are high [57]. However, efforts are being made to identify predictors of a positive response, and HSN is far from being completely clarified as pathophysiological effects and outcomes are concerned [58]. A recent study identified the physiological traits predictive of a good response to treatment: a low arousal threshold and loop gain, and occurrence of muscle compensation [59].…”
Section: Hypoglossal Nerve Stimulation (Hsn)mentioning
confidence: 99%
“…Although UAS surgery is safe from an assessment of perioperative risks, identifying which children are the best candidates for an implant is still a mystery. Studies evaluating the factors associated with successful therapy for adults cite the predictive value of body mass index and age; however, there is limited research evaluating the factors associated with adherence to therapy and successful long-term use, which was a gap identified in the International Sleep Surgical Society Research Forum . We hypothesize that children with severe sensory issues would be less likely to tolerate the device and that the existing adult literature does not take into account the sensory limitations that may be a significant barrier for this population.…”
mentioning
confidence: 96%
“…Studies evaluating the factors associated with successful therapy for adults cite the predictive value of body mass index and age; however, there is limited research evaluating the factors associated with adherence to therapy and successful long-term use, which was a gap identified in the International Sleep Surgical Society Research Forum. 2,5 We hypothesize that children with severe sensory issues would be less likely to tolerate the device and that the existing adult literature does not take into account the sensory limitations that may be a significant barrier for this population. For children who have persistent severe OSA following a UAS implant, management options are similar to those for adults and include confirming proper system function, device reprogramming, and consideration of adjunct treatments with UAS, including positional therapy, concurrent use of a mandibular advancement device, or the addition of supplemental oxygen via nasal cannula.…”
mentioning
confidence: 99%